Love in law$1 (Bs shadow: political theory, moral psychology and young Hegel$1 (Bs critique of punishments - Norrie, Alan (2019)
Modern theory of punishment conflates two types of question. The first concerns the justification of state punishment, the second the moral damage that occurs when a person is violated, and how the resulting damage can be repaired. The first question leads to political theory and a particular legally based moral grammar of wrongdoing and punishment. The second goes in the direction of a different moral psychology involving a grammar of violation, grieving and reconciliation. Retrieving the young Hegel$1 (Bs analysis takes us in the second direction. It provides a critical vantage point from which to view the dominant liberal political theory, including Hegel$1 (Bs own mature position as a founder of retributive theory. The modern theory of state punishment is legitimated by its public association with a moral psychology of violation, which it at the same time suppresses in favour of its own very different moral grammar. - Reproduced.s
Keywords: Punishment (Psychology); Political theory; Hegel